The increase in absolute theta power and the inhibition of light stimulus in cybersickness (Research, Society and Development, 2021)
Cybersickness results from the visual vestibule conflict, that is, the incoherence between the sensations related to real movement, in the virtual environment, and the visual stimuli. In response to the virtual environment, one can observe discomforts such as nausea, difficulty in concentrating, and headaches, among others. There are no studies in the literature that analyze the inhibition control of light stimuli in individuals sensitive to Cybersickness. Therefore, this study looked at the control of light stimulus inhibition in Cybersickness. The Sickness Susceptibility Questionnaire was used to divide the subjects into experimental and control groups, and quantify the signs and symptoms, comparing them before and after 3D virtual immersion and. Participants in both groups were examined with EEGq for absolute theta band power in the dorsolateral prefrontal cortex and ventrolateral prefrontal cortex during the light stimulus inhibition task before and after participants watched the 3D video. The partial results showed that there was an increase in the absolute theta band power in both groups comparing the moments before and after, as well as a significant difference in the experimental group compared to the control, for the same moment. Thus, it was observed that individuals who were exposed to 3D virtual reality and developed Cybersikness, showed greater absolute theta band power in the areas studied.